2010
DOI: 10.1007/s12011-010-8637-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multivitamin/Mineral Supplementation on Trace Element Levels in Serum and Follicular Fluid of Women Undergoing in Vitro Fertilization (IVF)

Abstract: We investigated effects of multivitamin/mineral supplementation on element levels in serum and follicular fluid of women undergoing IVF. We used three groups in this study. The first group was used as an age-matched and nonpregnant control (n = 13). Group 2 (n = 30) constituted the IVF group and women in the third group who were undergoing IVF also received a multivitamin/mineral tablet daily for 45 days. Follicular fluid and serum selenium and zinc levels and follicular fluid copper levels were lower in IVF p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 26 publications
(39 reference statements)
4
44
1
2
Order By: Relevance
“…They suggested that these molecules may be effective in quenching excessive generation of free radicals, but they do not seem to play a contributory role in achieving successful pregnancy following IVF. This is an important observation in view of the fact that several groups have the opinion that antioxidants, mineral and vitamin supplementation may considerably improve the IVF success rate [42,43]. However, our study conflicts with the results of some other studies [8,36,44], which observed that lower levels of antioxidants predict decreased fertilization potential.…”
Section: Discussioncontrasting
confidence: 95%
“…They suggested that these molecules may be effective in quenching excessive generation of free radicals, but they do not seem to play a contributory role in achieving successful pregnancy following IVF. This is an important observation in view of the fact that several groups have the opinion that antioxidants, mineral and vitamin supplementation may considerably improve the IVF success rate [42,43]. However, our study conflicts with the results of some other studies [8,36,44], which observed that lower levels of antioxidants predict decreased fertilization potential.…”
Section: Discussioncontrasting
confidence: 95%
“…The finding of increased le vels of Cu in OJ rats in our study was supported by the results of Devipriya et al (13). Excess cumulation of Cu in rats triggers oxidative damage of the kidney and liver tissue DNAs and ultimately contributes to many degenerative disorders (19). In this study we observed that OJ group had higher levels of serum and liver Cu, respectively (p<0.001 and p=0.003), than other groups.…”
Section: Discussionsupporting
confidence: 90%
“…Cu is an essential element that plays a role in the production of hemoglobin, myelin, collagen, and melanin [24]. Cu deficiency affects various physiological functions that may be important in immunological defense to pathogenic challenge [25,26]. Cu has also function as cofactor of SOD and CAT in antioxidant redox system [26,27].…”
Section: Discussionmentioning
confidence: 99%